Development of an Innovative Pocket Ampoule Cutter to Improve Nurses’ Self-Protection - Farrel Badzli; Supriyadi; Wahyu Riyaningrum; Rully Annisa (Jurnal Ilmiah Multidisiplin, 2026)
Nurses are the healthcare professionals who most frequently handle injectable medications packaged in glass ampoules. The conventional method of opening ampoules manually using fingers poses a risk of occupational injury, particularly cuts caused by sharp glass fragments. Therefore, innovation is needed to enhance nurses’ self-protection during the ampoule-opening procedure. This study aims to develop an innovative device called the Pocket Ampoule Cutter (PAC) to improve nurses’ self-protection. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The validation process involved three nursing experts and one occupational health and safety (OHS) expert, while the implementation stage involved ten nurses at RST Wijaya Kusuma Purwokerto. Data were collected using validation sheets and user evaluation questionnaires based on a Likert scale to assess aspects of safety, ease of use, comfort, design, material quality, maintenance, hygiene, and overall feasibility of the device. The validation results showed that the PAC achieved an average feasibility score of 95.83%, which falls into the “very feasible” category. Meanwhile, the implementation results based on nurses’ assessments showed an average score of 93.33%, also categorized as “very feasible.” These findings indicate that the PAC effectively improves nurses’ protection by minimizing direct hand contact with broken ampoule glass and facilitating a safer ampoule-opening procedure. In conclusion, the Pocket Ampoule Cutter (PAC) is considered a feasible, practical, and safe device that can enhance nurses’ self-protection during the ampoule-opening process.